Hubungan Peran Tenaga Kesehatan,Pengetahuan dan Dukungan Suami dengan Akseptor KB IUD di UPTD Puskesmas Pengandonan Kabupaten Ogan Komering Ulu - Trianingsih Trianingsih; Erma Puspita Sari; Siti Aisyah Hamid; Hasbiah Hasbiah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The IUD is one of the contraceptive methods that has a high effectiveness of IUD contraception installed in the uterus. Factors that affect IUD family planning acceptors include the role of health workers, knowledge, husband's support simultaneously at the pengandonan health center, Kab. Oku in 2021. This type of research is an analytical survey with a cross sectional design. The population in this study were family planning acceptors who visited the pengandonan health center from January to July 2021 totaling 247 people with a sample of 38 respondents using accidental sampling technique. The research instrument is a questionnaire, with univariate and bivariate data analysis (α = 95%). The results of the analysis were obtained from 38 respondents who used IUD KB (23.7%) and the role of health workers both who used IUD KB (15.8 %), good knowledge of using IUD KB (23.7%) while those who were supported by husbands of users KB IUD by (21.1%). Based on the bivariate analysis of the results of the chi-square test of the role of health workers (p-value = 0.001. knowledge (p-value = 0.002) and husband's support (p-value = 0.000), it was concluded that there was a relationship between the role of health workers, knowledge and support of husbands in the UPTD of the pengandonan health center in 2021. Suggestions for puskesmas It is hoped that health workers will play an active role again in providing counseling and counseling in every posyandu activity, distributing lieflet to every woman of childbearing age who visits the puskesmas so that the mother's knowledge becomes good